Drug reaction with eosinophilia and systemic symptom induced by carbamazepine: a case report - Damor, Rahul R.; Kubavat, Amita R.; Piparva, Kiran G. (International Journal of Basic & Clinical Pharmacology, 2019)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a severe, potentially life-threatening acute adverse drug reaction (ADR), typically characterized by a long latency period (2-6 weeks to 3 months) from drug exposure. DRESS syndrome is defined by the presence of fever, cutaneous eruption, lymphadenopathy, systemic or asymptomatic internal organ involvement (e.g. Hepatitis, carditis, interstitial nephritis, interstitial pneumonitis, etc.) and haematological abnormalities, mainly leucocytosis, eosinophilia and sometimes atypical lymphocytosis. There are around 50 culprit drugs which cause DRESS syndrome e.g. carbamazepine, phenytoin, allopurinol, sulfa derivatives, antidepressants, antiepileptics, non-steroidal anti-inflammatory drugs and antimicrobials. The incidence of DRESS syndrome has been estimated to be between 1 in 1,000 and 1 in 10,000 drug exposures. There are many reported cases of DRESS syndrome due to carbamazepine, phenytoin, vancomycin, levitiracitam, ceftriaxone etc. Author presented a case of DRESS syndrome by carbamazepin. RegiSCAR and Japanese consensus group have developed specific criteria for making the diagnosis of DRESS syndrome. The patient described here met the majority of criteria according to RegiSCAR scoring guidelines for a diagnosis of DRESS syndrome induced by carbamazepine. As per RegiSCAR diagnostic criteria author had concluded that this was a “Definite” case of DRESS (Drug Reaction with Eosinophilia and Systemic Symptom) syndrome induced by carbamazepine. Carbamazepine is most common broad-spectrum antiepileptic drugs so, this case report will raises awareness among physician to suspect DRESS syndrome in patients who present unusual complaints and skin findings after starting antiepileptic drugs.